VBScript and JScript used in ASP : from user's perspective / Marziani Mahmud - Mahmud, Marziani (2005)
Over the last few years the interest in scripting languages has dramatically increased. These languages have many important advantages over traditional programming languages. VBscript and Jscript are the most popular scripting languages use in Microsoft's Active Server Pages (ASP). ASP is one of the programming languages used to provide interactive and dynamic web pages. Interactive means that user and server can interact directly to each other and dynamic web pages is one that can change its contents without having to be rewritten each time. The research is to determine the scripting languages that most popular among students and lecturers at Faculty of Information Technology and Quantitative Sciences (FTMSK) UiTM Shah Alam. It is also identify which scripting language between VBscript and Jscript can develop more interactive and dynamic web pages. From this research, new developers can make it as a guideline in choosing the scripting language to write ASP pages. The language choices from most of the respondents that answer the questionnaire are VBscript since it is closely akin to Visual Basic and Visual Basic for Applications. However, for those respondents that are more familiar with C, C++ and Java, Jscript is a comfortable alternative for them. The primary differences between VBscript and Jscript are the syntax of the language, the sensitivity of the variables and supported browsers for the scripting. In the future these scripting languages are likely to become the core of most programming projects because of their power to combine existing components together into a working application system.